Laser Acceleration of Electrons in Magnetized Collisionless Plasma - Habeeb, Mohammed A Z; Yahya, Khalid A; Kneoy, Amal M (Al-Nahrain Journal of Science, 2018)
A computational investigation was carried out in the field of laser-plasma interaction to study the acceleration of electrons with non - relativistic velocities in magnetized collisionless plasma. The interaction of a Nd: Yag laser pulse of 25 fs duration and a 5x1015 W/cm2 intensity with a plasma was studied at a plasma electron density ne=1x1018 cm-3 in the presence of an external magnetic field for the three values of the field strength B=60 MG, 70 MG and 80 MG. It was found that the electron acquires a maximum energy of 19 keV during the interaction when an external magnetic field of strength B= 80 MG is applied. The maximum energy of the electron during the interaction reaches 1 keV in the absence of an external magnetic field for the same plasma electron density and laser pulse, after the interaction the maximum energy of the electron reached 15 eV. However, the maximum energy of the electron after the interaction reaches 3 keV when an external magnetic field strength of B= 70 MG is applied. This is due to a sustainable generated laser wakefield of 2x109 V/cm. Thus, it is concluded that an applied external magnetic field assists the acceleration of the electron and can subsidize for a high laser beam intensity.